Intermittent energy restriction vs. continuous energy restriction on cardiometabolic risk factors in patients with metabolic syndrome: a meta-analysis and systematic review - Xu, Rui; Cao, Youxiang; Wang, Peng-Ying; Chen, Xiao-Lan; Tao, Dan (Frontiers in Nutrition, 2023)
Background This is a systematic review and meta-analysis to compare the efficacy of intermittent energy restriction (IER) versus continuous energy restriction (CER) on weight loss, body composition, blood pressure, and other cardiometabolic risk factors in patients with metabolic syndrome (MetS) risk factors. Methods We searched and screened PubMed, Embase, Cochrane Library, and Web of Science from inception to May 8, 2022 for randomized controlled trials. Two review authors independently selected studies, extracted data, assessed quality and risk of bias and cross-checked extracts to resolve discrepancies when required. We expressed effect size as mean difference (MD) and 95% confidence interval (CI). The major outcome was the improvement of MetS risk factors, including changes in waist circumference (WC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-c), blood pressure (BP), and fasting plasma glucose (FPG) levels. The secondary outcomes were body weight (BW), body mass index (BMI), body fat (BF), fat free mass (FFM), hip circumference (HC), fasting insulin (FINs), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-c). Results The meta-analysis included 16 articles (20 trials) with a total of 1,511 participants. All studies had a low risk of bias for random sequence generation. The IER and CER intervention equally improved MetS risk factors WC (MD = -0.47, 95%CI [-1.19, 0.25]), TG (MD = -0.02 mmol/L, 95%CI [-0.11, 0.07]), FPG (MD = -0.02 mmol/L, 95% CI [-0.10, 0.05]) and BP (systolic blood pressure: MD = 0.93 mmHg, 95%CI [-2.74, 4.61]; diastolic blood pressure: MD =1.15 mmHg, 95%CI [-0.24, 2.55]), but HDL-c (MD = 0.03 mmol/L, 95%CI [0.01, 0.05]) was significant improved in IER when compared with CER. For second outcomes, BW (MD = -0.8 kg, 95%CI [-1.26, -0.33]), BF (MD = -0.75 kg, 95%CI [-1.73, -0.13]) and FFM (MD = -0.49 kg, 95%CI [-0.92, -0.05]) were also significant improved in IER, and not for other outcomes. Conclusion Both IER and CER could improve MetS biomarkers, but IER was more effective than CER in the improvement of HDL-c only. For secondary outcomes, IER was also more effective for BW, BF and FFM, but there were no differences in effects for other outcomes.